Moving on from Ebla, I crossed the Euphrates : an Assyrian day in honour of Paolo Matthiae - Nadali, Davide; Nigro, Lorenzo; Pinnock, Frances; Matthiae, Paolo (Archaeopress Archaeology, 2022)
Six articles by leading scholars on the culture of the Assyrian world pay homage to Paolo Matthiae, known internationally for the discovery of the site of ancient Ebla in Syria. The articles deal with different aspects of Assyrian culture, with innovative and sometimes unexpected points of view, including its reception in the modern world.